Analisis Tingkat Kesehatan Bank Dengan Menggunakan Motode CAMEL Pada PT. Bank Rakyat Indonesia Cabang Bajawa - Bupu, Maria Eufrasia; Tanusi, Gabriel; Dua Mea, Maria Helena Carolinda (Program Studi Manajemen Universitas Flores, 2021)
The purpose of this study was to analyze to determine the soundness level of the bank using the CAMEL method at PT. Bajawa People's Bank. This research is quantitative descriptive. This research was conducted at PT. Bank Rakyat Indonesia, Bajawa Branch. The data collection techniques used were interviews and literature study. The data analysis technique is the CAMEL method (capital, assets, management, earnings and liquidity). The results of this study indicate that the level of health at Bank Rakyat Indonesia, Bajawa Branch, is 1) The soundness level of the bank in terms of capital cannot be calculated because the capital structure is presented on a consolidated basis. 2) The soundness level of the bank in the aspect of productive asset quality (KAP) PT. Bank Rakyat Indonesia, Bajawa Branch is included in the very healthy category with an average of 0.9828%. 3) The soundness level of the bank from the management aspect uses the net profit margin ratio at PT. Bank Rakyat Indonesia Bajawa Branch is included in the very healthy category with an average of 112.56%. 4) The soundness level of the bank in terms of profitability, both in the ROA and BOPO ratios, the results of the calculation of the ROA ratio for the last three years have fluctuated, so the ROA ratio is categorized in the healthy group with an average of 5.506%. The results of the calculation of the BOPO ratio are fluctuating from year to year. Then this ratio is categorized in the unhealthy group with an average of 373.64%. 5) The soundness level of the bank from the liquidity aspect of the ratio of the calculation of the loan to deposit ratio for three years, namely from year to year has increased. Then the results of the LDR calculation achieved by PT. Bank Rakyat Indonesia Bajawa Branch is categorized as unhealthy with an average of 132.65%.